APLIKASI PEMBELAJARAN LOGIKA MATEMATIKA BERBASIS ANDROID (Information Technology and Telematics, 2014)
ABSTRAKComputer science developed from mathematical logic that is used as the basis for learning programming languages , data  structures , artificial intelligence , engineering / digital systems , databases , komputansi theory , software engineering , expert systems , neural networks , and others who use logic intensively. The goal is to make math learning application logic that is able to deliver new innovations in the learning process and ease of using a mobile phone or media tablet based on Android . The design of learning application logic models in this study includes several working steps ranging from the manufacture of the program structure , form input / output user interface design , user interface design implementation into xml design,  implementation design of systems that have been created using the Java programming language with eclipse software , as well as perform system testing on the device 's application mobile. The result of this application is packaged in a Logic file Matematika.apk consisting of 19 activities in the form of a class . Java and 11 layouts in the form of a file . xml .Keywords : Learning , Mathematical Logic , Java , Eclipse , Android .